Exploring The Value of Struggle in The Inspirational Narratives Of Kip-Kuliah Recipients: A Sociological Literary Approach - Elma Indriyani; Ayu Febri Anitasari; Wiwik Fitriyani; Diyamon Prasandha (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
Kartu Indonesia Pintar Kuliah (KIP-Kuliah) is a government initiative designed to promote accessible education for all segments of society. In their pursuit of higher education, KIP-Kuliah recipients have faced numerous challenges, including financial constraints and limited educational opportunities. These struggles are captured in narrative texts that compile inspiring stories from KIP-Kuliah recipients. The narratives in these literary works reflect the lived experiences of the authors, showcasing the various aspects of their life challenges. The research focuses on 30 short stories written by KIP-Kuliah scholarship recipients, which were gathered during an inspirational story competition organized by the KBBi (Keluarga Besar Beasiswa) at Universitas Negeri Semarang in 2024. This study aims to represent the values of struggle in inspirational stories through an extensive analysis of these works using descriptive analysis. The research employs a qualitative descriptive method, concentrating on sociological literary analysis as a framework. Data collection techniques included interviews, reading, and note-taking. The data analysis technique was conducted in three stages: data reduction, data presentation, and conclusion deduction. The results of the analysis show that there are several values of struggle among KIP-Kuliah scholarship recipients, such as fortitude, patience, perseverance, determination, hard work, diligence, resolve, sacrifice, persistence, and optimism.